OPPORTUNITIES TO USE THE LACTOCONTAINING PROBIOTICS IN CHILDREN PRACTICES - L.N. Mazankova; T.A. Chebotareva; I.D. Maikova; L.V. Begiashvili ("Paediatrician" Publishers LLC, 2007)
The article characterizes the modern approach to the lacto containing probiotics application in the clinical practices. The authors clarify the mechanisms of the functional activity of the lacto bacteria, l. reuteri inclusive. It is recommended to use the lacto containing probiotics in the complex therapy for acute enteric infections, gastroenterological and allergic diseases, functional disorders of the gastrointestinal tract, secondary immunodeficiency states. Key words: probiotics, lacto bacteria, children, infectious and noninfectious diseases of the gastrointestinal tract, nutrition, immunity.